Chemical vs. Physical Methods to Improve Dermal Drug Delivery: A Case Study with Nanoemulsions and Iontophoresis - Ines Nikolić; Mitar Simić; Ivana Pantelić; Goran Stojanović; Jelena Antić Stanković; Bojan Marković; Snežana Savić (MDPI AG, 2022)
So far, various approaches have been proposed to improve dermal drug delivery. The use of chemical penetration enhancers has a long history of application, while methods based on the electrical current (such as iontophoresis) stand out as promising "active" techniques. Aiming to evaluate the contribution of different approaches to dermal delivery, in this work curcumin-loaded nanoemulsions with and without monoterpenes (eucalyptol or pinene) as chemical penetration enhancers, and a custom-made adhesive dermal delivery system based on iontophoresis were designed and assessed. In an in vivo study applying skin bioengineering techniques, their safety profile was proven. Three examined iontophoresis protocols, with total skin exposure time of 15 min (continuous flow for 15 min (15-0); 3 min of continuous flow and 2 min pause (3-2; 5 cycles) and 5 min of continuous flow and 1 min pause (5-1; 3 cycles) were equally efficient in terms of the total amount of curcumin that penetrated through the superficial skin layers (in vivo tape stripping) (Q3-2 = 7.04 ± 3.21 μg/cm2; Q5-1 = 6.66 ± 2.11 μg/cm2; Q15-0 = 6.96 ± 3.21 μg/cm2), significantly more efficient compared to the referent nanoemulsion and monoterpene-containing nanoemulsions. Further improvement of an efficient mobile adhesive system for iontophoresis would be a practical contribution in the field of dermal drug application.